Management of mandibular angle fractures using a 1.7 mm 3-dimensional strut plate - Varnika Pandey; Ongkila Bhutia; Shakil Ahmed Nagori; Ashu Seith; Ajoy Roychoudhury (Elsevier, 2016)
Aim: We report our experience with the use of 1.7 mm 3-dimentional (3D) strut plate for the management of mandibular angle fractures. Methods: This prospective study enrolled 15 patients in whom mandibular angle fractures were treated with 1.7 mm 3D plate using trans-buccal trochar. Patients were evaluated at 72 h, 2 weeks, 6 weeks and 12 weeks for fracture stability, occlusion, soft-tissue swelling, infection and post-operative inferior alveolar nerve damage. Other complications like wound dehiscence, non-union, mal-union and hardware failure were also assessed. Results: In the immediate post-operative period, fracture instability was seen in 1 (6.7%) patient which resolved by 2 weeks. Mild occlusal discrepancy was also noted in 1 (6.7%) patient. Wound dehiscence was seen in 5 (33.3%) patients and all resolved by local measures. 1 (6.7%) patient developed post-operative nerve paraesthesia. Immediate post-operative radiographic evaluation demonstrated optimal reduction in all cases with no inferior border gaping. No case of infection, hardware failure, non-union and mal-union was noted. Conclusion: Within the limitations of the study, 1.7 mm 3D strut plate was found to be effective for management of non-communited mandibular angle fractures.